Factors Influencing the Occurrence of Fraud : Employee Perceptions in the HG Business Group - Panata Bangar Hasioan Sianipar (The Accounting Journal of Binaniaga, 2022)
Fraud is an endless problem in the business world, a lot of research has been done to find out about fraud. This research is also to examine the factors as independent variables that affect the occurrence of fraud. The factors used are factors that exist in the general triangle theory, but for the elements of each factor it is different from several previous studies. This research was conducted in a business group that has geographically distant working areas, and the selected sample is also spread over each working area of the business group. The research method used is quantitative. In this research, it is known that the factors tested are not all significant in influencing employees to commit fraud. An interesting finding is the negative influence of the "Justification" variable on the causes of fraud, in addition to the insignificant "Opportunity" variable in influencing the occurrence of fraud. This research is expected to contribute to management in designing a supervisory model in companies whose operations are not located in one location. The implication of this research to the organization is that there are other factors other than the three factors that can influence the occurrence of fraud